Design of coal pillars of gob-side entry between mining faces with large differences in mining height in deep mine. Issue 21 (1st November 2020) - Qi, Wenyue; Zhang, Qiang; Zhang, Jixiong; Zhang, Jianguo; Zhu, Cunli
ABSTRACT: In order to solve the problems of large deformations of gob-side entry and the fracture of coal pillars at large-height mining faces in deep mines, a case study of the width design of coal pillars between a slice mining face and a large height mining face is studied by theoretical calculation, numerical analysis, and site engineering measurement. In this paper, the occurrence of the Ji16-17 coal seam and its mechanical properties are analyzed. In addition, driving disturbances on roadway deformations, and the effect of plastic area distributions under conditions of different widths of coal pillars and different falls in heights are studied when mining at a slice face turned to a large height face in a deep mine. The results show that the reasonable width of a coal pillar is 8 m with a fall in mining height of 2.5 m between the Ji16-17 –24011 slice face and the Ji16-17 − 24030 large mining height face (at a 5.5 m mining height). The monitored results show that at a mining height of 5.5 m, an 8 m panel pillar can effectively maintain the stability of a pillar and gob-side entry, and can meet the requirements for the safe production of a stable transition from the slice mining face to the large mining height face.